Determinants of internal audit efficiency - H. A. Kruger; P. J. Steyn; W. Kearney (South African Journal of Business Management, 2002)
This paper describes a case study in which Data Envelopment Analysis (DEA) methodology was combined with regression analysis to evaluate the efficiency of an Internal Audit (IA) department over twelve consecutive months. Efficiency of audit projects was first estimated using DEA. These results were then used as one of the outputs to perform a multi-period DEA study with a choice of other inputs and outputs specific to the Internal Audit department under review. The efficiency of audit projects is viewed as one of the key outputs of an IA department and an explanation of these efficiencies would therefore be useful (necessary) to enhance insights gained from the DEA model applied to the twelve months. To assist in this explanation a multiple regression model was employed in which the efficiency score obtained from the DEA computations for the audit projects was used as the dependent variable. Following a description of the models and data, the results are discussed and notes are made of certain aspects pertaining to the department reviewed.
Keywords: 650